Detection of T‐Wave Beat‐By‐Beat Variations prior to Ventricular Arrhythmias Onset in ICD‐Stored Intracardiac Electrograms: The Endocardial T‐Wave Alternans Study (ETWAS). Issue 11 (23rd July 2014) - MAURY, PHILIPPE; LIN, CHAO; PASQUIÉ, JEAN‐LUC; RACZKA, FRANK; BECK, LIONEL; TAIEB, JÉRÔME; MAILHES, CORINNE; TOURNERET, JEAN‐YVES; ROLLIN, ANNE; DUPARC, ALEXANDRE; MONDOLY, PIERRE; WINUM, PIERRE; et al.
<x xml:space="preserve">Abstract</x> Background The aim of the Endocardial T‐Wave Alternans Study was to prospectively assess the presence of T‐wave alternans (TWA) or beat‐to‐beat repolarization changes on implantable cardioverter‐defibrillator (ICD)‐stored electrograms (EGMs) immediately preceding the onset of spontaneous ventricular tachycardia (VT) or fibrillation (VF). Methods Thirty‐seven VT/VF episodes were compared to 116 baseline reference EGMs from the same 57 patients. A Bayesian model was used to estimate the T‐wave waveform in each cardiac beat and a set of 10 parameters was selected to segment each detected T wave. Beat‐by‐beat differences in each T‐wave parameter were computed using the absolute value of the difference between each beat and the following one. Fisher criterion was used for determining the most discriminant T‐wave parameters, then top‐M ranked parameters yielding a normalized cumulative Fisher score > 95% were selected, and analysis was applied on these selected parameters. Simulated TWA EGMs were used to validate the algorithm. Results In the simulation study, TWA was detectable even in the case of the smallest simulated alternans of 25 μV. In 13 of the 37 episodes (35%) occurring in nine of 16 patients, significant larger beat‐to‐beat variations before arrhythmia onset were detected compared to their respective references (median one positive episode per patient). Parameters including the T‐wave apex amplitude seem the more discriminant parameters. Conclusions Detection of beat‐by‐beat repolarization variations in ICD‐stored EGMs is feasible in a significant subset of cases and may be used for predicting the onset of ventricular arrhythmias.